2014
DOI: 10.1128/iai.01618-13
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bone Loss in Experimental Periodontitis Induced by Aggregatibacter actinomycetemcomitans in Interleukin-1 Receptor Antagonist Knockout Mice

Abstract: cThe interleukin-1 receptor antagonist (IL-1Ra) binds to IL-1 receptors and inhibits IL-1 activity. However, it is not clear whether IL-1Ra plays a protective role in periodontal disease. This study was undertaken to compare experimental periodontitis induced by Aggregatibacter actinomycetemcomitans in IL-1Ra knockout (KO) mice and wild-type (WT) mice. Computed tomography (CT) analysis and hematoxylin-and-eosin (H&E) and tartrate-resistant acid phosphatase (TRAP) staining were performed. In addition, osteoblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 63 publications
(66 reference statements)
2
32
0
1
Order By: Relevance
“…Thus, a study of IL-1ra knockout mice showed a greater antigenic response to A . actinomycetemcomitans infection, with an increased production of pro-inflammatory cytokines, rapid loss of alveolar bone (assessed by micro-CT), lesser formation of mineralized matrix, and greater tissue expression of bone resorption markers[33]. Our results are compatible with the conclusion of Yucesoy et al that an imbalance of the IL-1β/IL-1ra ratio in periodontal tissue appears to reduce susceptibility to periodontitis [34].…”
Section: Discussionsupporting
confidence: 90%
“…Thus, a study of IL-1ra knockout mice showed a greater antigenic response to A . actinomycetemcomitans infection, with an increased production of pro-inflammatory cytokines, rapid loss of alveolar bone (assessed by micro-CT), lesser formation of mineralized matrix, and greater tissue expression of bone resorption markers[33]. Our results are compatible with the conclusion of Yucesoy et al that an imbalance of the IL-1β/IL-1ra ratio in periodontal tissue appears to reduce susceptibility to periodontitis [34].…”
Section: Discussionsupporting
confidence: 90%
“…In line with prior studies, the secretion of IL-1␤ and IL-18 was extensively enhanced when MG63 cell cultures were challenged with the bacteria (Kelk et al, 2011;Belibasakis and Johansson, 2012). The excessive pro-inflammatory response triggered by A. actinomycetemcomitans contributes significantly to alveolar bone loss in periodontitis (Izawa et al, 2014).…”
Section: Discussionsupporting
confidence: 65%
“…Mice lacking IL-1Ra in all tissues or only cell type-specifically Increased severity of IMQ-induced skin inflammation [176] in myeloid cells are more susceptible to lethal endotoxemia [157,158] as well as to inflammatory bone loss in bacterial peridontitis [159]. In contrast, mice lacking IL-1Ra have an improved survival upon infection with Listeria monocytogenes [157].…”
Section: Il-1ra Deficiencymentioning
confidence: 97%